Antiviral therapy of acute respiratory viral infection and influenza in children in a hospital - E. V. Sharipova (Žurnal Infektologii, 2018)
Objective: to study the efficacy and safety of antiviral therapy for influenza and acute respiratory viral infection with Kagocel in children in a hospital. Materials and methods: in the observational study included 80 children aged 3 to 11 years, hospitalized with symptoms of influenza and acute respiratory viral infection. The etiological confirmation of the diagnosis was carried out by the PCR method based onthe study of nasal swabs.The drug Kagocel was administered according to the instructions for use during the first 24 hours of hospitalization.The analysis of the virus release after the course of therapy with Kagocel (at 5–6 days from the beginning of treatment) was carried out only in patients with verified influenza and acute respiratory viral infection. Results: the dominant influence of viruses in the development of acute respiratory infections in children aged 3 to 11 years in the period of rising morbidity in St. Petersburg from September 2015 to May 2016. At the same time, 25% of the total number of patients were sick with influenza A and/or B. There was a significant decrease in fever to the third day (p <0,001) and normalization of body temperature from the fourth day after the beginning of therapy with Kagocel in the general group and in patients with confirmed influenza diagnosis. The intoxication syndrome, most pronounced with the flu, was mostly stopped by the fourth day(р<0,001). Catarrhal syndrome, prevalent in the general group of acute respiratory viral infection, had longer periods of clinical manifestation and against the background of the therapy completely eliminated to the third or seventh day of therapy.Negative PCR results after the course of Kagocel therapy were established in 57,1% of the total group of patients. Among all detected viruses, the most typical is the absence of repeated isolation of influenza B and A viruses, PC virus (86% and 53,8%, 71,4%, respectively), the elimination of rhinoviruses was less frequent (33,3%). Conclusion: according to the results of the study, the effectiveness of therapy with the inclusion of the drug Kagocel in relieving fever by 3–4 days of treatment, as well as intoxication syndrome by 5–6 days in patients with acute respiratory viral infections, including patients with influenza, has been established. Negative results of PCR at the time of completion of therapy occurred mainly in patients with influenza A and B, PC infection. No adverse events were noted.